A Investigação e a Escrita: Publicar sem Perecer - Sequeiros, Paula; José Carvalho, Maria; Capinha, Graça (Coimbra University Press, 2025)
Research and Writing: Publish do not Perish is a collection of texts published in Portuguese, based on the problematization of a five-year experience of advanced extracurricular training in information literacy, writing and scientific publication (i.e., Publish do not Perish: Survive the Stampede). It is a questioning of the role of science in a context that appears to reproduce neoliberalism and the commodification of academia. This work results from the collaboration of national and international authors who consider a diversity of theoretical and empirical fields that deal with that phenomenon. This book aims to identify and question the subsequent problems, trying to point out solutions to the growing malaise in the academic world.